Development of Deep Learning-Oriented Google Sites Interactive Learning Media to Support SDG 4: Quality Education in High School English Learning - Rosnilawati; Alwen Bentri; Zelhendri Zen; Mutiara Felicita Amsal; Rayendra (Jurnal Penelitian Pendidikan IPA, 2026)
English learning at the high school level still faces various challenges, such as time constraints, low interaction, and the dominance of one-way learning that does not support 21st century skill development. This research aims to develop Google Sites-based interactive learning media that is oriented towards deep learning to improve understanding of concepts and student engagement. This research uses the Research and Development (R&D) method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The subjects of the study were 36 students of class X Phase E at SMAN 7 Padang. The research instruments include expert validation sheets, practicality questionnaires, and learning outcome tests. The data were analyzed descriptively, quantitatively, and qualitatively and used the N-gain test to measure effectiveness. The results showed that the media developed had a validity level of 95% (very feasible category), a practicality level of 95% (teachers) and 90% (students) (very practical category), and high effectiveness with an increase in average score from 58.7 (pretest) to 89.72 (posttest) and an N-gain value of 0.80 (high category). These findings show that Google Sites-based interactive learning media oriented to deep learning has proven to be valid, practical, and effective in improving students' understanding of concepts in English learning.